The Dynamics Impact of Urban Area on the River Health in Surakarta City - Firdausi, Eyda; Matin, Hashfi Hawali Abdul; Budiyono, Budiyono; Wahyono, Yoyon; Othman, Nur Hidayati (Universitas Diponegoro, 2025)
Surakarta City is traversed by the Bengawan Solo River Sub-Basin which includes Kali Pepe River, Gajah Putih River, Kali Anyar River, Jenes River, and Premulung River. This condition results in the main burden of river water pollution coming from anthropogenic activities, both domestic and industrial. This study aims to examine the influence of urban area dynamics on river health with a case study of Surakarta City. This study used qualitative descriptive method. Data collection was carried out through observation techniques, and depth interviews. The results showed that there are three factors that affect river health, namely population increase, industrial and domestic activities, and public perception and participation. Surakarta City is one of the areas that contributes to river pollution from moderate to severe levels. However, there have been many efforts to evaluate river health by the local government, namely by normalizing riverbanks, controlling waste pollution, and other river management programs.